Предмет: Математика,
автор: yliakorotchenko
4(x + 1) < 3(x - 3) - *, 4(2x - 1)
Приложения:
![](https://files.topotvet.com/i/f31/f31f26472a731a9f0756ac00028873da.jpg)
Ответы
Автор ответа:
0
Ответ:
Пошаговое объяснение:
4(х + 1) < 3(х - 3) - х
4(2х - 1) ≤ 3(3х - 2)
4х + 4 < 3х - 9 - х
8х - 4 ≤ 9х - 6
4х - 3х + х < -9 - 4
8х - 9х ≤ -6 + 4
2х < -13
-х ≤ -2
х < -13/2
х ≥ 2
х < -6,5
х ≥ 2
х Є ∅
Пошаговое объяснение:
4(х + 1) < 3(х - 3) - х
4(2х - 1) ≤ 3(3х - 2)
4х + 4 < 3х - 9 - х
8х - 4 ≤ 9х - 6
4х - 3х + х < -9 - 4
8х - 9х ≤ -6 + 4
2х < -13
-х ≤ -2
х < -13/2
х ≥ 2
х < -6,5
х ≥ 2
х Є ∅
Похожие вопросы
Предмет: Технология,
автор: valyabrazhnik1
Предмет: Окружающий мир,
автор: okcali
Предмет: Русский язык,
автор: Нияз2014
Предмет: Биология,
автор: bagdandaudov
Предмет: Математика,
автор: Ученикточкару